ANALISIS PEMBIAYAAN MUDHARABAH PADA PT. BANK SUMUT KCP SYARIAH STABAT ( Tinjauan Fiqih Muamalah) - Ayu Liviana; Anjur Perkasa Alam; Azhar (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
The purpose of this study was to determine the process of financing the mudharabah contract at PT. Bank Sumut Kcp Syariah Stabat. To find out the review of Fiqh Muamalah on the process of financing the mudharabah contract at PT. Bank Sumut Kcp Syariah Stabat. To find out the products that exist at Bank Sumut Kcp Syariah Stabat which sell mudharabah contracts. This type of qualitative research is used in this study using descriptive analysis methods. Descriptive analysis is used to explore the collected data and describe clearly the problems and research results. Data collection is done through observation, interviews or structured interviews, and documentation. The results of this study indicate that financing in general is the provision of money or an equivalent claim, based on an agreement or agreement between the bank and another party that requires the party being financed to return the money or bill after a certain period of time with a reward or profit sharing. The principle of mudaraba, the depositor acts as shahibul maal (owner of capital) and the bank as mudharib (manager). The funds are used by the bank to finance murabahah or ijarah as previously described. The bank can also use the funds to carry out mudharabah financing. The results of this business will be divided according to the agreed ratio. In the event that the bank uses it to carry out mudharabah financing, the bank is fully responsible for the losses that occur. The pillars of mudharabah are perfectly fulfilled (there are mudharib, there are owners of funds, there is a business that will be shared, there is a ratio, there is consent and acceptance). This mudharabah principle is applied to time deposit and time deposit products.